(untitled) (CIPEEX, 2025)
This study examines the pas de nullité sans grief principle enshrined in article 563 of the Brazilian Code of Criminal Procedure, under which a procedural act is void only upon proof of actual prejudice. It is a doctrinal and case-law review that systematizes criteria for assessing procedural harm and for controlling formal defects. The aim is to indicate, in practical terms, when procedural flaws substantially affect prosecution or defense rights so as to justify invalidation. The method consisted of analyzing textbooks and precedents that relate prejudice review to truth-seeking and procedural efficiency, distinguishing harmless irregularities from errors capable of undermining the decision. The findings show that: (i) nullity is not presumed and does not flow automatically from formal defects; (ii) the party alleging nullity must concretely demonstrate the link between the defect and the impairment of procedural rights; and (iii) the judge must provide reasons for the prejudice assessment in light of the evidentiary context. It concludes that a restrictive, well-reasoned application of the principle preserves procedural regularity without sacrificing effectiveness, avoiding pointless annulments and promoting materially just decisions.